Unlocking Purchasing Decisions through Quality, Price, and the Role of Social Media in Indonesia: Membuka Keputusan Pembelian melalui Kualitas, Harga, dan Peran Media Sosial di Indonesia - Fahim Ridho Irawan; Lilik Indayani (Academia Open, 2024)
This study explores the combined influence of product quality, price, and social media utilization on purchasing decisions. Using a quantitative approach, data were collected from 97 consumers in Sidoarjo Regency who purchased nylon thread from CV. BUMI HIJAU PLAST through questionnaires and analyzed using SPSS16. The results demonstrate that all three factors significantly impact purchasing decisions. These findings suggest that consumers should consider these elements in their decision-making process, and businesses can enhance their marketing strategies by focusing on these key factors. Highlights: Product quality, price, social media significantly impact purchasing decisions. Data collected from 97 consumers, analyzed with SPSS16. Businesses should focus on these factors to improve marketing. Keywords: Product quality, price, social media, purchasing decisions, consumer behavior